Chemical composition (Proximate Analysis) and oil content of jatropha curcas seed with different maturity/ Juplin Kinti, Margaret Chan & Lydia Dundun Francis - Kinti, Juplin; Chan, Margaret; Francis, Lydia Dundun (2011)
Jatropha curcas is classified as one of the plant oil similar to palm oil and has potential as a renewable energy crop as its oil may be used directly with slow speed diesel engine or upgraded via transesterification to conventional biodiesel. The assessment of performance and benefits of Jatropha curcas in relation to its oil content and oil quality is based on extrapolation of its potentials by multiplying observation from singular or small plots to plantations on a per hectare base. In addition, it is reported that plants from Jatropha curcas seeds have a large biological variation.The objectives of the study are to determine the oil content of seeds at different maturity as indicated by the colour of the fruits and to compare the oil content of seeds from four different cultivars.